2019
DOI: 10.3390/medicina55050175
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thyroid Stimulating Hormone Level Within the Reference Range on In-Hospital and Short-Term Prognosis in Acute Coronary Syndrome Patients

Abstract: Background and objectives: Despite being within the normal reference range, changes in thyroid stimulating hormone (TSH) levels have negative effects on the cardiovascular system. The majority of patients admitted to hospital with acute coronary syndrome (ACS) are euthyroid. The aim of this study was to investigate the effect of TSH level on the prognosis of in-hospital and follow-up periods of euthyroid ACS patients. Materials and Methods: A total of 629 patients with acute coronary syndrome without thyroid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“… 26 It was found that high-normal level of TSH is an independent predictor for mortality during 6 months hospitalization in euthyroid sick syndrome. 27 …”
Section: Abnormal Thyroid Hormone Status During Critical Illnessmentioning
confidence: 99%
“… 26 It was found that high-normal level of TSH is an independent predictor for mortality during 6 months hospitalization in euthyroid sick syndrome. 27 …”
Section: Abnormal Thyroid Hormone Status During Critical Illnessmentioning
confidence: 99%
“…Ndrepepa et al ( 9 ) enrolled 8,010 patients treated with PCI and found that the TSH level was associated with 30-day mortality but not with 30-day to 3-year mortality. Gürdoğan et al ( 14 ) reported that the high-normal TSH group in euthyroid acute coronary syndrome (ACS) patients was an independent predictor for mortality during the 6-month follow-up. However, Åsvold et al ( 15 ) analyzed 14 cohorts, including 55,412 patients with the TSH level within the reference range and no previously known thyroid or cardiovascular disease at baseline and concluded that TSH levels within the reference range were not associated with risk of cardiovascular events or CAD mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Inoue et al ( 32 ) have reported that a U-curved association between TSH and the risk of all-cause mortality in the cohort study of 9,020 US adults and higher TSH levels (>1.96 mIU/l) were associated with increased risk of all-cause mortality. Gürdoğan et al ( 14 ) reported that the high-normal TSH group (>1.60 μIU/ml) in ACS patients was an independent predictor for mortality during the 6-month follow-up. Evidence shows that although the serum TSH level reflects thyroid–pituitary feedback, it might not be efficient enough to show thyroid status in every organ ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Meanwhile, abnormal thyroid hormones including free triiodothyronine (FT3) and free tetraiodothyronine (FT4), along with thyroid stimulating hormones (TSH) have been found to play pleiotropic roles in the progress of CAD, through oxidative stress, endothelial dysfunction, lipid metabolism and insulin resistance-related mechanisms, etc. 3,4,10,11 However, only a limited number of studies have concerned about the impacts of these hormones on CAD within normal reference range, which was the most common condition in the real-world clinical settings, 12,13 and results remained controversial. [13][14][15][16][17] Diabetes mellitus and thyroid dysfunction are the two most common endocrine disorders, and both of them contribute to the development of CAD.…”
Section: Introductionmentioning
confidence: 99%